2017
DOI: 10.1007/s10948-017-4452-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface Effects on the Dynamic Behavior of Vortices in Type II Superconducting Strips with Periodic and Conformal Pinning Arrays

Abstract: Using molecular dynamics techniques, we simulate the vortex behavior in a type II superconducting strip in the presence of triangular and two types of conformal pinning arrays, one with a pinning gradient perpendicular to the driving force (C1) and the other parallel (C2), at zero temperature. A transport force is applied in the infinite direction of the strip, and the magnetic field is increased until the rate between the density of vortices (n v ) and pinning (n p ) reaches n v /n p = 1.5. Our results show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 96 publications
(154 reference statements)
0
2
0
Order By: Relevance
“…Theoretical studies demonstrated that the size effects influence properties like magnetization, vortex lattice geometry, critical currents, and dynamical phases for superconducting strips [45][46][47][48][49][50][51][52][53]. As an example, Carneiro [45] analyzed the minimum energy configuration for several vortex lattices in superconducting thin strips, observing changes in the vortex configuration with the increase of the applied magnetic field.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies demonstrated that the size effects influence properties like magnetization, vortex lattice geometry, critical currents, and dynamical phases for superconducting strips [45][46][47][48][49][50][51][52][53]. As an example, Carneiro [45] analyzed the minimum energy configuration for several vortex lattices in superconducting thin strips, observing changes in the vortex configuration with the increase of the applied magnetic field.…”
mentioning
confidence: 99%
“…The explanation for this effect is that the attractive pinning potential in the sample induces the vortex penetration at lower values of magnetic field. Recently, Vizarim et al [53] also showed that the vortex penetration may be influenced on how the pinning centers are distributed in the sample.…”
mentioning
confidence: 99%